Drivers of peatland water table dynamics in the central Andes, Bolivia and Peru. Issue 13 (7th April 2019) - Cooper, David J.; Sueltenfuss, Jeremy; Oyague, Eduardo; Yager, Karina; Slayback, Daniel; Caballero, E. Marcelo Cabero; Argollo, Jaime; Mark, Bryan G.
Abstract: Cushion plant dominated peatlands are key ecosystems in tropical alpine regions of the Andes in South America. The cushion plants have formed peat bodies over thousands of years that fill many valley bottoms, and the forage produced by the plants is critical for native and nonnative domesticated mammals. The sources and flow paths of water supporting these peatlands remain largely unknown. Some studies have suggested that glacier meltwater streams support some peatlands, and that the ongoing loss of glaciers and their meltwaters could lead to the loss or diminishment of peatlands. We analysed the hydrologic regime of 10 peatlands in four mountain regions of Bolivia and Peru using groundwater monitoring. Groundwater levels in peatlands were relatively stable and within 20 cm of the ground surface during the rainy season, and many sites had water tables 40–90 cm below the ground surface in the dry season. Topographic and groundwater elevations in the peatlands demonstrated that the water source of all 10 peatlands was hillslope groundwater flowing from lateral moraines, talus, colluvium, or bedrock aquifers into the peatlands. There was little to no input from streams, whether derived from glacier melt or other sources, and glacier melt could not have recharged the hillslope aquifers supporting peatlands. We measured the stable water isotopes in water samples taken during different seasons, distributed throughout the catchments, and the values are consistent with this interpretation. Our findings indicate that peatlands in the study region are recharged by hillslope groundwater discharge rather than stream water and may not be as vulnerable to glacial decline as other studies have indicated. However, both glaciers and peatlands are susceptible to changing thermal and precipitation regimes that could affect the persistence of peatlands.